Residential electricity subsidies in Mexico : exploring options for reform and for enhancing the impact on the poor. - Komives, Kristin (World Bank working paper ;, 2009)
Large and growing subsidies to residential consumers in Mexico have become a major policy concern. This report explains the growth of subsidies, the current distribution of subsidies across income classes, and uses utility and household survey data to simulate how alternative subsidy mechanisms could improve distributional and fiscal performance. The goal is to help inform discussion in Mexico about how to reduce subsidies and redirect them toward the poor. The findings also offer lessons for other countries that are planning tariff reforms in their electricity sectors.